Tradisi Siram Tuwuh Perspektif ‘Urf: (Studi di Kelurahan Warujayeng Tanjunganom Nganjuk) - Maryam Qurotul Aini, Siti; Maulidin, Sifa’ul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
The Siram Tuwuh tradition generally means tajdid nikah, which in Javanese means mbangun nikah, bilas nikah, and ngenyari nikah. The Siram Tuwuh tradition in Warujayeng Village, Tanjunganom, Nganjuk is still preserved by some people. The motivations of those who carry out the Siram Tuwuh tradition are factors of faith and parental orders. With the hope that carrying out this tradition will create a happy family, avoid disaster and as a form of gratitude. The practice of the Siram Tuwuh tradition in Warujayeng Village, Tanjunganom, Nganjuk is in the form of a thanksgiving ceremony by inviting neighbors and relatives. The motivations of those who carry out the Siram Tuwuh tradition are factors of faith and parental orders, with the aim that if they carry out the Siram Tuwuh tradition, their family will be given happiness, long-lasting, blessed fortune and be kept away from disaster. The tradition of siram tuwuh in Warujayeng Village, Tanjunganom Nganjuk, when analyzed using the theory of 'urf', is considered 'urf sahih' (authentic) because it does not conflict with Islamic law and does not harm the participants or the community. Therefore, the tradition of siram tuwuh in Warujayeng Tanjunganom Nganjuk is permissible to preserve as long as it does not conflict with the texts of the Qur'an and Hadith.